Transition‐metal‐catalyzed Chelation‐assisted C–H Functionalization of Aromatic Substrates. Issue 2 (10th March 2016) - Zhao, Binlin; Shi, Zhuangzhi; Yuan, Yu
Abstract: In the past decade, transition‐metal‐catalyzed C–H activations have been very popular in the research field of organometallic chemistry, and have been considered as efficient and convenient strategies to afford complex natural products, functional advanced materials, fluorescent compounds, and pharmaceutical compounds. In this account, we begin with a brief introduction to the development of transition‐metal‐catalyzed C–H activation, especially the development of transition‐metal‐catalyzed chelation‐assisted C–H activation. Then, a more detailed discussion is directed towards our recent studies on the transition‐metal‐catalyzed chelation‐assisted oxidative C–H/C–H functionalization of aromatic substrates bearing directing functional groups. Abstract : Transition‐metal‐catalyzed chelation‐assisted C–H activation provides atom‐ and step‐economical approaches for the construction of functional compounds. In this account, a more detailed discussion is directed towards our recent studies of the transition‐metal‐catalyzed chelation‐assisted C–H/C–H functionalization of aromatic substrates bearing directing functional groups.